Teaching Arabic Language Base on Character Building Through Qur'an Perspective - Sanusi, Anwar; Albantani, Azkia Muharom (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2021)
This study aims to reinforce character building through the Qur’an perspective during Arabic teaching and learning processes at MA Al-Musdariah 2 Cimahi, Indonesia. There are six principles of politeness in language use in Qur’an, namely; qaulan sadidan, ma’rufan, balighan, maysuran, layyinan, dan kariman. The research method used in this study was phenomenology, scientific approach, and formal juridical approach. This study was classified as a descriptive qualitative study. The results of this study showed that in terms of Arabic lessons plan, they were not properly and perfectly implemented the reinforcing of politeness in language use in the light of Qur’an perspective. Whilst, in terms of teaching and learning activities including opening, core, closing and evaluating activities, they reflected several principles of politeness in language use namely; truth, honesty, fairness, kindness, being straight, smoothness, politeness, appropriateness, being respectful, solemnity, optimism, beauty, fun, logic, fluency, clearness, precision, meaningfulness, harmony, being impressive, calmness, effectiveness, gentleness, and being humble.